L. MIHAILESCU-BÎRLIBA, RURE VIVERE IN MOESIA INFERIORE. LA POPULATION DANS LE MILIEU RURAL D’UNE PROVINCE PÉRIPHERIQUE DE L’EMPIRE ROMAIN - Rada Varga (Journal of Ancient History and Archaeology)
The present submission is a review of L. Mihailescu-Bîrliba’s book on the rural areas of Moesia Inferior. The book is an exhaustive and comprehensive overview of the population attested in here during the Roman period. Besides putting together all sources on this matter, it offers an analytic insight into the social, economic and cultural realities of the province’s rural inhabitants.